Protection of Whistleblowers under Czech Law within the Context of the Directive on the Protection of Persons Who Report Breaches of Union law (2019/1937) - Morávek, Jakub; Pichrt, Jan (Towards a Better Protection of Workplace Whistleblowers in the Visegrad Countries, France and Slovenia, 2021)
The chapter is focused on the protection of whistleblowers under Czech law within the context of the Directive on the protection of whistleblowers for persons who report breaches of Union law (2019/1937). Specifically, the chapter deals with all seven previous and current proposals for legal regulation of whistleblower protection. The authors provide a detailed discussion of the current draft of law to transpose Directive 2019/1937. The authors deal with the definition of the scope of the bill, retaliation measures, breadth of the obligation to implement a notification system, status of the responsible/concerned person in the notification system, absence of motivational measures and problematic aspects of public control.